Synthesis of a bio-based plasticizer from oleic acid and its evaluation in PVC formulations. (December 2016) - Omrani, Ismail; Ahmadi, Abbas; Farhadian, Abdolreza; Shendi, Hasan Kashef; Babanejad, Niloofar; Nabid, Mohammad Reza
Abstract: The bio-based plasticizers have been extensively developed due to their high compatibility and low toxicity. In this study, the bio-based plasticizers of methyl 10-(2-methoxy-2-oxoethansulfonyl) octadecanoate (MDA) and ethyl 10-(2-ethoxy-2-oxoethanesulfonyl) octadecanoate (EDA) were synthesized from the oleic acid and thioglycolic acid and characterized by 1 HNMR and FT-IR. The prepared materials were applied as plasticizers in Poly(vinyl chloride) (PVC) and their properties were compared with the commercial plasticizer, Bis(2-ethylhexyl) phthalate (DOP). The viscosities of prepared plastisols from novel designed plasticizers were lower than DOP. The results of mechanical properties showed that the synthesized plasticizers of MDA and EDA have the ability of plasticizing effects similar to DOP on PVC. Thermogravimetric analysis (TGA) indicated that both MDA and EDA have higher thermal stability than DOP. Two polar ester as well as polar sulfone groups in the chemical structure of MDA and EDA led to lower migration, volatility and exudation than DOP.